PENGARUH MEDIA FLIPBOOK GAMBAR BERSERI TERHADAP KETERAMPILAN MEMBACA PEMAHAMAN SISWA SANGGAR BIMBINGAN KEPONG MALAYSIA - Rahma, Fanisha Alya; Nasution, Dewi Kesuma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the low reading comprehension skills of students at Sanggar Bimbingan Kepong, Malaysia. One of the influencing factors is the lack of engaging learning media. This study aims to analyze the effect of flipbook with sequential images on improving students' reading comprehension skills. The research method used was a one-group pre-test post-test design with a sample of 10 students. Data were analyzed using validity test, reliability test, normality test, and hypothesis test. The results showed that the research instrument was valid and reliable, with a Cronbach’s Alpha value of 0.824. The normality test indicated that the pre-test and post-test data were normally distributed. The hypothesis test using the paired sample t-test showed a significant difference between the pre-test (70.70) and post-test (81.90) scores, with a significance value of 0.000 (<0.05). This proves that using a flipbook with sequential images positively impacts students' reading comprehension skills.